Patients' and physicians' gender and perspective on shared decision-making: A cross-sectional study from Dubai. - Mohamad Alameddine; Farah Otaki; Karen Bou-Karroum; Leon Du Preez; Pietie Loubser; Reem AlGurg; Alawi Alsheikh-Ali (PLoS ONE, 2022)
Background Delivering patient-centered care is a declared objective of many health delivery systems globally, especially in an era of value-based health care. It entails the active engagement of the patients in healthcare decisions related to their health, also known as shared decision making (SDM). Little is known about the role of gender in shaping the perspective of patients on their opportunity for engaging in SDM in the Arabian Gulf Region. The aim of this study is to investigate the role of gender in shaping patients' perspectives toward their opportunity for SDM in Dubai, UAE. Methods This study utilized a cross-sectional survey consisting of sociodemographic questions and the 9-item Shared Decision-Making Questionnaire (SDM-Q-9). A total of 50 physicians (25 females and 25 males), practicing at a large private healthcare delivery network in Dubai, were recruited using convenience sampling. Ten patients of every recruited physician (5 male and 5 female) were surveyed (i.e., a total of 500 patients). Statistical analysis assessed the differences in patients' perceptions of physician SDM attitude scores by physicians' and patients' gender using independent t-test, ANOVA-test, and Chi-square analyses. Findings A total of 50 physicians and 500 patients (250 male patients and 250 female patients) participated in this study. The odd of patients agreement was significantly lower for male physicians, compared to their female counterparts, on the following elements of SDM: the doctor precisely explaining the advantages and disadvantages of the treatment (OR = 0.55, 95%CI: 0.34-0.88, p = 0.012); the doctor helping them understand the information (OR = 0.47, 95%CI: 0.23-0.97, p = 0.038), the doctor asking about preferred treatment option (OR = 0.52, 95%CI: 0.35-0.77, p = 0.001), and the doctor thoroughly weighting the different treatment options (OR = 0.60, 95%CI: 0.41-0.90, p = 0.013). No significant associations were observed between patients' gender and their perception of their opportunity for SDM. Likewise, no significant associations were observed between the same or different physician-patient gender and patients' perception of physicians' SDM attitudes. Statistically significant associations were observed between physician-patient gender and preferred treatment option for patients (p = 0.012). Conclusion Study findings suggest that while there were no differences in patients' perspective on SDM by the gender of patients, significant differences were observed by the gender of physicians. Female physicians, compared to their male counterparts, were more engaged in SDM, with both male and female patients. Male physician-female patient dyad received the lowest scores on SDM. This could be explained by the cultural, social, and religious sensitivities that infiltrate the physician-patient relationship in the Arab contexts. Despite the multi-cultural nature of the country, some female patients may still experience some discomfort in opening up and in discussion preferences with male physicians. For physicians, striking the right balance between assertiveness and SDM is necessary within the cultural context, especially among male providers. Offering targeted learning and development programs on the importance and practice of SDM is also necessary to ensure equitable opportunity for engagement in SDM for all patients irrespective of the gender of their provider.